2007
DOI: 10.2215/cjn.00670207
|View full text |Cite
|
Sign up to set email alerts
|

Low Urine pH

Abstract: Background and Objectives: The metabolic syndrome is associated with alterations in renal function. An overly acidic urine has been described as a renal manifestation of the metabolic syndrome in patients with kidney stone disease. This study examined the association between the metabolic syndrome and urine pH in individuals without a history of nephrolithiasis.Design, Setting, Participants, & Measurements: A total of 148 adults who were free of kidney stones were evaluated in this outpatient cross-sectional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
180
5
9

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 258 publications
(212 citation statements)
references
References 36 publications
9
180
5
9
Order By: Relevance
“…Other studies that investigated the effect of an acid/base imbalance on health focused on bone and kidney stones [9,10]. Associations between low serum bicarbonate, higher anion gap and low urine pH-all markers of metabolic acidosis-and insulin resistance have been reported [7,19,20]. Higher levels of serum lactate, a component of the anion gap, have been associated with a higher risk of type 2 diabetes in the ARIC cohort [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies that investigated the effect of an acid/base imbalance on health focused on bone and kidney stones [9,10]. Associations between low serum bicarbonate, higher anion gap and low urine pH-all markers of metabolic acidosis-and insulin resistance have been reported [7,19,20]. Higher levels of serum lactate, a component of the anion gap, have been associated with a higher risk of type 2 diabetes in the ARIC cohort [20].…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been suggested that acid/base imbalance may play an important role in some cardiometabolic abnormalities [3][4][5]. Markers of diet-induced metabolic acidosis have been associated with insulin resistance, but only in crosssectional studies [6][7][8], preventing any conclusions in terms of causality. Moreover, type 2 diabetes incidence and glucose intolerance have been shown to be higher in people with a lower urinary pH than in those with a higher urinary pH [9].…”
Section: Introductionmentioning
confidence: 99%
“…Diet exposures and physical activity were calculated as updated cumulative average levels as of the baseline (1990) questionnaire. We also summarized intake of cereal fibre and trans fats, glycemic load and the ratio of polyunsaturated to saturated fats (with each component categorized in quintiles and scored 1-5, where 5 was assigned to the healthiest intake) in a diabetes diet score (ranging from [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20], with a high diet score associated with a reduced risk of type 2 diabetes mellitus in the Nurses' Health Study. 16 The reproducibility and validity of the food-frequency questionnaires have been described.…”
Section: Assessment Of Covariatesmentioning
confidence: 99%
“…8 In addition, higher levels of serum lactate, a small component of the anion gap, were associated with higher odds of prevalent type 2 diabetes mellitus in the Atherosclerosis Risk in Communities study 9 and with higher odds of incident type 2 diabetes mellitus in a retrospective cohort study of the risk factors for diabetes in Swedish men. 10 Other biomarkers associated with metabolic acidosis, including higher levels of serum ketones, 11 lower urinary citrate excretion 12 and low urine pH, 13 have been associated in crosssectional studies with either insulin resistance or the prevalence of type 2 diabetes mellitus. However, it is unclear whether these associations are a cause or consequence.…”
mentioning
confidence: 99%
“…Cross-sectional and metabolic studies have demonstrated a link between insulin resistance, a hallmark of type 2 diabetes, and low urine pH (8,9). Obesity, a common finding in patients with type 2 diabetes, is also associated with lower urine pH (10,11).…”
mentioning
confidence: 99%